Need Assessment of Islamic Teaching Materials Character-Based Entrepreneurship in University - Badawi, Badawi; Prihatmojo, Agung; Elizar, Elizar; Kuning, Dewi Sri (Letiges, 2023)
The implementation of entrepreneurship education emphasizes the cognitive aspect, so it has not created the entrepreneurial character yet. Besides, the unavailability of teaching materials for students related to entrepreneurship education in achieving learning outcomes. This study aims to obtain an overview of the needs assessment for preparing character-based entrepreneurship teaching materials at the University of Muhammadiyah Kotabumi. The method used was qualitative research based on the post-positivism philosophy. Data collection techniques were observations, interviews and documentation studies by testing the validity of the data using triangulation. The results of this study can be seen from the aspects of material substance (Excellent character, The character of the Prophet Muhammad in business, and Character of a Successful Entrepreneur From Zero), content structure aspects (Introduction, Presentation, and Closing), presentation and linguistic factors (Attractive presentation, Accuracy, Digestibility, Illustrations, and Completeness), assignment aspects (Observation, Making a business plan, and Entrepreneurial practice) and character-based question types (Assignments, Midterm exams, and Semester exams). This study indicates the need for character-based entrepreneurship teaching materials with the substance of character-based teaching materials using structures, criteria, question forms and assignments in university entrepreneurship teaching materials.